2021
DOI: 10.1145/3449154
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Ignore

Abstract: Bulk email is a primary communication channel within organizations, with all-company emails and regular newsletters serving as a mechanism for making employees aware of policies and events. Ineffective communication could result in wasted employee time and a lack of compliance or awareness. Previous studies on organizational emails focused mostly on recipients. However, organizational bulk email system is a multi-stakeholder problem including recipients, communicators, and the organization itself. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The IDF uses the log to dampen the impact of high-frequency terms [98]. In the review study by Kong et al [86] enclosed are the management strategies to control the trafficking of the bulk email related to the promotion and advertisement of the organization or the media. The uncontrolled feedback on the product makes the user tired and wastes the time the user goes through every email.…”
Section: Discussionmentioning
confidence: 99%
“…The IDF uses the log to dampen the impact of high-frequency terms [98]. In the review study by Kong et al [86] enclosed are the management strategies to control the trafficking of the bulk email related to the promotion and advertisement of the organization or the media. The uncontrolled feedback on the product makes the user tired and wastes the time the user goes through every email.…”
Section: Discussionmentioning
confidence: 99%
“…Dabbish et al surveyed 128 employees of a university and found that employees prioritized the emails from the senders that they had a direct work relationship with [13]. Kong et al [30] interviewed the recipients, managers, and communicators of a university. They found that the managers and communicators thought that employees should know about what was going on in the university.…”
Section: Organizational Communication and Bulk Email's Goalsmentioning
confidence: 99%
“…In this paper, we focus on 2 kinds of stakeholders: the organization leaders and communicators who represent the organization's perspective, and the normal employees who represent the recipients' perspective on messages' work-relevance/interest/importance level. The organization and employees may have different perspectives [30,51]. For example, the university's board of regents might want all the employees to know about their meeting updates; then they put it as the first message of the Brief with the hope that all the employees who opened this Brief will notice this message (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that there is a gap of priorities amongst the different stakeholders, which challenges the acceptability of dynamic information technology. For example, the technology innovators j MEASURING BUSINESS EXCELLENCE j may consider blasting emails from social media to provide crucial high-level information, whilst the firms did not view the bulk message in social media as essential information (Kong et al, 2020).…”
Section: Information Technological Turbulencementioning
confidence: 99%